2023
DOI: 10.2340/actadv.v103.2558
|View full text |Cite
|
Sign up to set email alerts
|

Similar Levels of Disease Severity Correspond to a Greater Burden of Illness in Women Compared with Men with Hidradenitis Suppurativa

Abstract: is missing (Short communication)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…In this study, Sampogna et al (2008) found a significant difference in Skindex-29 scores, with worse outcomes for women in items #2, #6, #11, #12, #13, #15, #26, #28, and for the whole emotions and functioning subscale (p < 0.05), but not for the symptom's subscale. This result is in accordance with previous research on gender differences in chronic autoimmune dermatology patients (Samela et al, 2023).…”
Section: Differences Among Genders Detected In Skin Disease Quality O...supporting
confidence: 93%
“…In this study, Sampogna et al (2008) found a significant difference in Skindex-29 scores, with worse outcomes for women in items #2, #6, #11, #12, #13, #15, #26, #28, and for the whole emotions and functioning subscale (p < 0.05), but not for the symptom's subscale. This result is in accordance with previous research on gender differences in chronic autoimmune dermatology patients (Samela et al, 2023).…”
Section: Differences Among Genders Detected In Skin Disease Quality O...supporting
confidence: 93%
“…It is notable that, in that study, the findings were independent of HS severity ( 2 ). HS may be a very embarrassing disease with serious consequences, and patients with HS, especially females, consider the burden of HS to be very high ( 22 ), and have also been reported to have an increased risk of suicide regardless of whether they have a previous psychiatric diagnosis ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…As stated by the position statement of the European Academy of Dermatology and Venereology task forces on Quality of Life and Patient-Oriented Outcomes (12), among the specialty-specific PROMS, HS illness load has been predominantly assessed by the Dermatology Life Quality Index (DLQI), the Skindex-17, and the Skindex- 29 (13-15). Some recent studies are stressing the idea that the level of disease severity does not always correspond to the same illness load in HS measured with different PROMS (16)-as already highlighted for other chronic skin conditions (17,18)-and the idea that HS is a very debilitating condition, even at lower levels of clinical severity (15). Regardless of disease severity, as measured with the International Hidradenitis Suppurativa Severity Score System (IHS4) (19), patients with HS often go through the disruption of their personal and social life because of their disease (i.e., especially because of pain, suppuration, and discomfort due to abscesses), as documented by scores obtained in Skindex-17 subscales (15).…”
Section: Introductionmentioning
confidence: 99%